Analisis Hadis-Hadis Inses Dalam Perspektif Ilmu Medis (Kajian Sanad dan Matan) - Feriawan, Feriawan (UIN Sumatera Utara Medan, 2024)
This research aims to identify the quality of sanad and matan hadith incest and provide a review of medical science on incest. This research is a qualitative research in the form of a literature study. The primary data sources used in this study are the books of kutubu tis'ah. The analysis technique used by the author is the study of sanad and matan. The results of this study reveal that; 1) the quality of sanad and matan hadith about the prohibition of incestuous marriage; A marriage between a man and a woman who still has a very close blood relationship where including milk in terms of quality, the above hadith is included in the sahih hadith, because it meets the requirements of the sahih hadith and is also classified as a hadith that is al-Muttashil Marfu'. 2) The closer the kinship level, the more likely they are to get the same faults (weaknesses) in their genes, because they are inherited from the same parents. Because of this, a brother and a sister are more likely to have the same fault in their genes, a child resulting from such a sibling relationship can inherit the same bad gene in the same gene pair of both, resulting in two bad copies of the gene and serious damage.